2022
DOI: 10.1093/nsr/nwac269
|View full text |Cite
|
Sign up to set email alerts
|

The temporal dynamics of antimicrobial-resistant Salmonella enterica and predominant serovars in China

Abstract: Salmonella enterica is one of the most common bacterial pathogens in humans and animals. Systematic studies on the trends and geographical distribution of antimicrobial-resistant-Salmonella and dominant serovars have been well studied in European and American countries while not in China. Here, taking the One-Health strategy, we used > 35,000 Salmonella enterica isolates to explore the temporal and spatial dynamics of dominant serovars in China. We found that Salmonella Typhimurium was the dominant sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
1
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 75 publications
2
42
1
1
Order By: Relevance
“…Foodborne outbreak cases of Salmonella Goldcoast were mainly reported in Europe before [12][13][14][15] ; however, they have been increasingly observed in both the Chinese mainland and Taiwan, China nowadays 16,17 . Considering an emerging Salmonella serovar associated with human infections in China, One Health scale genomic tracking for S. Goldcoast was performed.…”
Section: Impact Statementmentioning
confidence: 99%
“…Foodborne outbreak cases of Salmonella Goldcoast were mainly reported in Europe before [12][13][14][15] ; however, they have been increasingly observed in both the Chinese mainland and Taiwan, China nowadays 16,17 . Considering an emerging Salmonella serovar associated with human infections in China, One Health scale genomic tracking for S. Goldcoast was performed.…”
Section: Impact Statementmentioning
confidence: 99%
“…To date, Salmonella strains are classified into 6 subspecies containing over 2,500 serovars ( 9 ). Several serovars, such as Typhimurium, Enteritidis, and Derby, are well-known as they are frequently detected in China and the other parts of the world ( 10 14 ). For example, a recent study analyzed 35,382 serotyped Salmonella in China between 1982 and 2019, and found Typhimurium was the most dominant serovar in the country, followed by Enteritidis and Derby ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several serovars, such as Typhimurium, Enteritidis, and Derby, are well-known as they are frequently detected in China and the other parts of the world ( 10 14 ). For example, a recent study analyzed 35,382 serotyped Salmonella in China between 1982 and 2019, and found Typhimurium was the most dominant serovar in the country, followed by Enteritidis and Derby ( 10 ). In addition, the proportion of Typhimurium and other serovars, including London, Rissen, Corvallis, Meleagridis, Kentucky, and Goldcoast, displayed an increasing prevalence from 2006 to 2019 ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, over 2500 Salmonella serotypes have been identi ed. S. Typhimurium and S. Enteritidis accounts for the majority of Salmonella infections in humans (5). Alarmingly, the emergence of multi-drug-resistant (MDR) Salmonella serotypes, particularly against 3rd-generation cephalosporins and uoroquinolones, is having a great impact on the e cacy of antibiotic treatment, and an increasing prevalence of MDR strains may lead to an increase in mortality rates of Salmonella infections(6).…”
mentioning
confidence: 99%